Pulmonary-renal syndrome secondary to cocaine-levamisole-induced vasculitis : A case report (2020)
ABSTRACT: Pulmonary-renal syndrome has rarely been reported as the clinical presentation of vasculitis caused by the consumption of cocaine adulterated with levamisole. We report the case of a patient in whom we detected the clinical manifestations and indicate the difficulties that arose in relation to the diagnostic and therapeutic approach.